Preparation and Characterization of PANI/PVA Electrochromic Membrane (Journal of Fiber Bioengineering and Informatics, 2014)
A facile strategy for obtaining Polyaniline (PANI) composites was reported wherein the reaction isoxidation polymerization using Dodecylbenzene Sulfonic Acid (DBSA) as the initiator, Polyvinyl Alcohol(PVA) as the emulsifier, and the Ammonium Peroxydisulfate (APS) as the oxidizing agent. The structureand performance of PANI composites were investigated. The results indicated that PANI particles can bedispersed evenly in the PVA matrix, the conductivity and electrochemical properties of the PANI/PVAcomposites were affected by the protonic acid content, When n(DBSA)/n(AN) = 1.0 under the samecondition, the conductivity of PANI membrane is up to 1.28 S/cm. From the FTIR spectrum, thecharacteristic peaks of PANI at 1459 cm^{-1} and 1697 cm^{-1} are attributed to the C = C stretchingvibration peak of the quinone ring and the benzene ring and the C = N stretching vibration peak of thequinone ring. The asymmetric ECD of PANI/PVA composites with copper and silver fabrics have boththree brilliant colors (green - blue - yellow primary colors).